Factors shaping the implementation of educational organizational change: An analysis of Lewin's model in the context of teaching innovations - Haneen Vasel (Social Sciences and Humanities Open)
The study examined factors influencing the implementation of educational organizational change based on pedagogical innovations, in this case, playful pedagogy, inquiry-based learning, and outdoor classroom learning, analyzing the process through the lens of Kurt Lewin's model. The research used a qualitative case study methodology to engage 28 Arab-Israeli elementary school teachers and a school principal. Data collection included 31 individual interviews, 28 with teachers and three with the principal, as well as three focus groups. The findings showed teachers' pedagogical perceptions and beliefs, linked to cultural factors, were critical in shaping their readiness to embrace change. Cultural influences, such as traditionalism and conservatism, could heighten resistance, creating significant challenges during the initial phase of organizational change. Factors influencing the change process included the nature of the change, the teachers involved, and the broader school context. Parent perceptions, the principal's leadership style, Ministry of Education policies, and aspects related to the teaching profession were also essential for successful implementation. Barriers included feelings of stagnation and inadequate support. The research highlights the complex interplay of cultural, pedagogical, and organizational factors influencing educational change, particularly within the Arab community in Israel. It provides insights into mechanisms that can hinder or facilitate reform, offering strategies for educational leaders to navigate challenges and foster a more innovative environment.